2007
DOI: 10.1302/0301-620x.89b4.18470
|View full text |Cite
|
Sign up to set email alerts
|

Embolic phenomena during computer-assisted and conventional total knee replacement

Abstract: Systemic emboli released during total knee replacement have been implicated as a cause of peri-operative morbidity and neurological dysfunction. We undertook a prospective, double-blind, randomised study to compare the cardiac embolic load sustained during computer-assisted and conventional, intramedullary-aligned, total knee replacement, as measured by transoesophageal echocardiography. There were 26 consecutive procedures performed by a single surgeon at a single hospital. The embolic load was scored using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 32 publications
4
41
0
Order By: Relevance
“…First, VTE could be initiated during the operation [35,36], in the postoperative period without mobilization [37], or 1-2 months after surgery [38,39]. Thus, evaluations of VTE occurrence may vary depending on the timing of imaging tests, duration of follow-up, or the duration of postoperative thromboprophylaxis.…”
Section: Fibrinolysis and Thrombolysis 170mentioning
confidence: 99%
“…First, VTE could be initiated during the operation [35,36], in the postoperative period without mobilization [37], or 1-2 months after surgery [38,39]. Thus, evaluations of VTE occurrence may vary depending on the timing of imaging tests, duration of follow-up, or the duration of postoperative thromboprophylaxis.…”
Section: Fibrinolysis and Thrombolysis 170mentioning
confidence: 99%
“…Studies do exist which show reduced blood loss [14,28,29], fewer systemic emboli [24,30,31] and fewer clinically detectable thromboembolic events [32] in navigated TKA compared with conventional TKA, and this is thought to be directly related to the avoidance of femoral and/or tibial intramedullary instrumentation. Cohorts in all these studies were, however, very small and offer low levels of evidence, and contradictory evidence does exist showing no difference in blood loss [25,33] and thromboembolic phenomena [13] between the two groups.…”
Section: Mortality and Morbiditymentioning
confidence: 99%
“…The risk of fat embolism during knee replacement has been shown to be significantly reduced when an extramedullary femoral alignment guide [27] or computerassisted surgery is used [7,15]. Studies using non-invasive [15] and invasive monitoring [7] have shown that significantly fewer emboli are detected in the systemic circulation during computer-assisted TKR compared with conventional TKR.…”
Section: Embolic Eventsmentioning
confidence: 99%
“…Studies using non-invasive [15] and invasive monitoring [7] have shown that significantly fewer emboli are detected in the systemic circulation during computer-assisted TKR compared with conventional TKR. However, most studies comparing these two methods have not shown any significant difference in post-operative thromboembolic events [2].…”
Section: Embolic Eventsmentioning
confidence: 99%